Raja Perempuan Zainab Ii Hospital, Kota Bharu,Kelantan Ambulatory Care Centre (Acc) & Haemodialysis Unit Project Planning Concept - Mohd Nawawi, Norwina ([s.n.], 2008)

(untitled)
A write up on the planning layout of the proposed Ambulatory Care Centre and Haemodialysis Unit of RPZII Hospitalin Kota Bharu, Kelantan for clarity of planning rationale through circulation pattern of staff, patient, services and supplies; its adjoining department, unit and spaces relationship; its inter-connectivity with adjacent existing main hospital building and parking facilities.